Silk fibroin micro-particle scaffolds with superior compression modulus and slow bioresorption for effective bone regeneration - Nisal, Anuya; Sayyad, Raeesa; Dhavale, Prachi; Khude, Bhakti; Deshpande, Rucha; Mapare, Vidhyashri; Shukla, Swati; Venugopalan, Premnath (Scientific Reports, 2018)
Silk fibroin (SF), a natural polymer produced by Bombyx mori silkworms, has been extensively explored to prepare porous scaffolds for tissue engineering applications. Here, we demonstrate, a scaffold made of SF, which exhibits compression modulus comparable to natural cancellous bone while retaining the appropriate porosities and interconnected pore architecture. The scaffolds also exhibit high resistance to in-vitro proteolytic degradation due to the dominant beta sheet conformation of the SF protein. Additionally, the scaffolds are prepared using a simple method of microparticle aggregation. We also demonstrate, for the first time, a method to prepare SF micro-particles using a Hexafluoroisopropanol-Methanol solvent-coagulant combination. SF microparticles obtained using this method are monodisperse, spherical, non-porous and extremely crystalline. These micro-particles have been further aggregated together to form a 3D scaffold. The aggregation is achieved by random packing of these microparticles and fusing them together using a dilute SF solution. Preliminary in-vitro cell culture and in-vivo implantation studies demonstrate that the scaffolds are biocompatible and they exhibit the appropriate early markers, making them promising candidates for bone regeneration.

Silk fibroin and ceramic scaffolds: comparative in vitro studies for bone regeneration - Deshpande, Rucha; Shukla, Swati; Sayyad, Raeesa; Salunke, Shalmali; Nisal, Anuya; Venugopalan, Premnath (Bioengineering & Translational Medicine, 2021)
Synthetic bone void fillers based on calcium ceramics are used to fill cavities in the bone and promote bone regeneration. More recently, silk fibroin (SF), a protein polymer obtained from Bombyx mori silkworm, has emerged as a promising material in bone void filling. In this work, we have compared the safety and efficacy of two types of silk fibroin-based bone void fillers with currently used and commercially available ceramic bone void fillers (based on calcium sulphate, beta tricalcium phosphate, and beta tricalcium phosphate with hydroxyapatite). Further, we have also evaluated these two types of SF scaffolds, which have strikingly different structural attributes. The biocompatibility of these scaffolds was comparable as assessed by cytotoxicity assay, cellular adhesion assay, and immunogenic assay. Ability of the scaffolds to support differentiation of human mesenchymal stem cells (hMSCs) into an osteoblastic lineage was also evaluated in an in vitro differentiation experiment using reverse transcriptase polymerase chain reaction analysis. These results revealed that cells cultured on SF scaffolds exhibit higher expression of early to late markers such as Runx2, BMPs, collagen, osterix, osteopontin, and osteocalcin as compared with ceramic-based scaffolds. This observation was further validated by studying the expression of alkaline phosphatase and calcium deposition. We also show that scaffolds made from same material of SF, but characterized by very different pore architectures, have diverse outcome in stem cell differentiation.
Keywords: beta tricalcium phosphate; bone regeneration; bone void filler; calcium sulphate; hMSCs; hydroxyapatite; osteoblasts; scaffold; Silk fibroin

Silk fibroin microparticle scaffold for use in bone void filling: safety and efficacy studies - Deshpande, Rucha; Shukla, Swati; Kale, Amod; Deshmukh, Narendra; Nisal, Anuya; Venugopalan, Premnath (ACS Biomaterials Science & Engineering, 2022)
Silk fibroin (SF) is a natural biocompatible protein polymer extracted from cocoons of silkworm Bombyx mori. SF can be processed into a variety of different forms and shapes that can be used as scaffolds to support bone regeneration. Threedimensional (3D) SF scaffolds have shown promise in bone-void -filling applications. In in vitro studies, it has been demonstrated that a microparticle-based SF (M-RSF) scaffold promotes the differentiation of stem cells into an osteoblastic lineage. The expression of differentiation markers was also significantly higher for M-RSF scaffolds as compared to other SF scaffolds and commercial ceramic scaffolds. In this work, we have evaluated the in vitro and in vivo biocompatibility of M-RSF scaffolds as per the ISO 10993 guidelines in a Good Laboratory Practice (GLP)-certified facility. The cytotoxicity, immunogenicity, genotoxicity, systemic toxicity, and implantation studies confirmed that the M-RSF scaffold is biocompatible. Further, the performance of the MRSF scaffold to support bone formation was evaluated in in vivo bone implantation studies in a rabbit model. Calcium sulfate (CaSO4) scaffolds were chosen as reference material for this study as they are one of the preferred materials for bone-void -filling applications. M-RSF scaffold implantation sites showed a higher number of osteoblast and osteoclast cells as compared to CaSO4 implantation sites indicating active bone remodeling. The number density of osteocytes was double for M-RSF scaffold implantation sites, and these M-RSF scaffold implantation sites were characterized by enhanced collagen deposition, pointing toward a finer quality of the new bone formed. Moreover, the M-RSF scaffold implantation sites had a negligible incidence of secondary fractures as compared to the CaSO4 implantation sites (similar to 50% sites with secondary fracture), implying a reduction in postsurgical complications. Thus, the study demonstrates that the M-RSF scaffold is nontoxic for bone-void -filling applications and facilitates superior healing of fracture defects as compared to commercial calcium-based bone void fillers.
Keywords: Biocompatibility; biological safety; bone void filler; ISO 10993; M-RSF; Serioss; Silk fibroin